Hydrogen and oxygen stable isotopes contributions for Brazilian aquifers knowledge: state of art and future perspectives - Gastmans, Didier [UNESP]; Garpelli, Lia Nogueira [UNESP]; dos Santos, Vinícius [UNESP]; de Lima, Camila [UNESP]; Quaggio, Carolina Stager [UNESP]; Santarosa, Lucas Vituri [UNESP]; Kirchheim, Roberto Eduardo (Derbyana, 2021)
HYDROGEN AND OXYGEN STABLE ISOTOPES CONTRIBUTIONS FOR BRAZILIAN AQUIFERS KNOWLEDGE: STATE OF ART AND FUTURE PERSPECTIVES. Groundwater supplies circa 50% of all Brazilian municipalities, and its increasing use results from the combination of (i) climatic conditions, as the high precipitation rates lead to important water surpluses, providing conditions to the recharge of aquifers, and (ii) the hydrogeological framework, consisting of a variety of aquifers (porous, fractured and karst) encompassed by different geological and structural provinces. Due to the importance of groundwater to Brazil, H and O stable isotopes have been regularly used in hydrogeological studies since the 1970’s, with an increase in the application of stable isotope methods at the beginning of the 21st century. This increase is associated with the establishment of numerous research groups in hydrogeology and the development of analytical techniques that enabled the optimization of the analyses. In this sense, we present a review of the application of H and O stable isotopes to the hydrogeological study of Brazilian aquifers, based on a critical reading of the available scientific literature. This paper is divided into five chapters. Initially, the theoretical foundations for the application of stable H and O isotopes in hydrological studies are presented, followed by a review of the knowledge about the rainwater isotopic composition and climatic controls. Then, the state-of-the-art of the application of stable isotopes in Brazil is complemented with the lessons learned and the opportunities revealed for the application of the methods in hydrogeological studies. This review attested the good coverage of rain water data and corresponding isotopic composition, allowing considerations at the regional scale, despite the time lag that occurred due to the interruption of the meteorological observations in the 1980’s. Regarding groundwater isotopic composition, the major variations were observed in regional aquifers, especially in confined portions, such as the aquifers of the Paraná Basin and of the Amazon Basin, reflecting past recharge conditions extending for long periods of time. The relationships between isotopic composition and regional climatic aspects and geographic localization are also reflected in the groundwater isotopic composition. Despite the growing number of studies using stable H and O isotopes, especially involving the most important sedimentary aquifers, there are still challenges those open new possibilities of study. There is a gap in knowledge regarding a holistic view about the water movement along the hydrological cycle, based on the understanding of the correlation between large-scale climatic phenomena and groundwater recharge, as well as the application of multi-isotopic tracer methods (involving noble gases and radioactive isotopes, for example), in order to determine groundwater residence times and water mixing, in addition to studies aiming at the understanding of groundwater-surface water interactions.
CONTRIBUIÇÃO DOS ISÓTOPOS ESTÁVEIS DA ÁGUA (H E O) NO CONHECIMENTO DOS AQUÍFEROS BRASILEIROS: ESTADO DA ARTE E PERSPECTIVAS FUTURAS
Keywords: Aquifers; Brazil; Groundwater; Water stable isotopes